PENILAIAN EKONOMI JASA LINGKUNGAN HUTAN KOTA PADA KAWASAN UNIVERSITAS TANJUNGPURA PONTIANAK - Juita, Sumyndra; Lumangkun, Augustine; Dewantara, Iswan (JURNAL HUTAN LESTARI, 2016)
The role of forest as a provider of environment services gives significant contribution. due to its capability in providing water resource, carbon storage, and natural services. Tanjungpura University has several potential areas as urban forest. These are Â Arboretum Untan, Jogging Track Untan, and Faculty of Forestry.It is important to value the urban forest economically so people will know the important benefit resulted by forest in term of money. The purposes of this research were to know the total economic value of urban forest related to environmental services, based on Direct Use Value (DUV), Indirect Use Value (IUV), and Option Value (OV). The research used descriptive method of sampling using accidental sampling technique and data collection stands by census. The value method used is analysis total economic valuation. Based the results research are Direct Use Value Rp 29.896.803,-, Indirect Use Value Rp 7.123.160.127 and Option Value Rp 578.708.120,-. Total Economic Valuation Rp 7.732.365.050,- / year. Keywords: Urban Forest, Environment Services, Total Economic Valuation